Using Stable Carbon Isotopes of Seasonal Ecosystem Respiration to Determine Permafrost Carbon Loss. Issue 1 (12th January 2019) - Mauritz, M.; Celis, G.; Ebert, C.; Hutchings, J.; Ledman, J.; Natali, S. M.; Pegoraro, E.; Salmon, V. G.; Schädel, C.; Taylor, M.; Schuur, E. A. G.
Abstract: High latitude warming and permafrost thaw will expose vast stores of deep soil organic carbon (SOC) to decomposition. Thaw also changes water movement causing either wetter or drier soil. The fate of deep SOC under different thaw and moisture conditions is unclear. We measured weekly growing‐season δ 13 C of ecosystem respiration (Recoδ 13 C) across thaw and moisture conditions (Shallow‐Dry; Deep‐Dry; Deep‐Wet) in a soil warming manipulation. Deep SOC loss was inferred from known δ 13 C signatures of plant shoot, root, surface soil, and deep soil respiration. In addition, a 2‐year‐old vegetation removal treatment (No Veg) was used to isolate surface and deep SOC decomposition contributions to Reco. In No Veg, seasonal Recoδ 13 C indicated that deep SOC loss increased as the soil column thawed, while in vegetated areas, root contributions appeared to dominate Reco. The Recoδ 13 C differences between Shallow‐Dry and Deep‐Dry were significant but surprisingly small. This most likely suggests that, under dry conditions, soil warming stimulates root and surface SOC respiration with a negative 13 C signature that opposes the more positive 13 C signal from increased deep SOC respiration. In Deep‐Wet conditions, Recoδ 13 C suggests reduced deep SOC loss but could also reflect altered diffusion or methane (CH4 ) dynamics. Together, these results demonstrate that frequent Recoδ 13 C measurements can detect deep SOC loss and that plants confound the signal. In future studies, soil profile δ 13 C measurements, vegetation removal across thaw gradients, and isotopic effects of CH4 dynamics could further deconvolute deep SOC loss via surface Reco. Plain Language Summary: Carbon (C) stored in permafrost soil is like a global savings account that keeps C out of the atmosphere. Arctic warming makes permafrost soil C vulnerable to microbial decomposition, and C released to the atmosphere would accelerate global warming. In this study we used 13 C isotopes, which function like molecular fingerprints, to detect permafrost soil C decomposition from a soil warming experiment that doubled the thawed soil volume and changed soil moisture conditions. We found that permafrost soil C decomposition was best detected when vegetation was removed. Deeper thaw depth had only a small effect on isotopic signatures possibly because the signal from higher permafrost soil C decomposition was overwhelmed by a simultaneous increase in surface soil decomposition and respiration from plants. In wet areas, the isotopic signal changed which could imply reduced permafrost soil C decomposition. In wet areas, methane cycling might also change the isotope signature. We conclude that seasonal 13 C sampling could be useful for detecting permafrost soil C decomposition if combined with measurements that can isolate contributions from surface soil, roots, and methane cycling. Developing methods that make it easier to assess permafrost soil C decomposition is critical for estimating the balance of our global C savings account. Key Points: Vegetation removal shows deep soil C loss does increase with thaw, and plant contributions to Reco dilute delta 13 C signals from deep soil Seasonal Reco delta 13 C suggests warming and permafrost thaw may stimulate deep soil respiration and also surface soil and plant respiration Wet conditions may reduce deep soil C loss, with possible effects of altered diffusion dynamics and increased methane cycling on delta 13 C